2020
DOI: 10.3390/nu12082434
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Fish-Derived Protein Hydrolysates on Metabolic Health, Skeletal Muscle Mass and Function in Ageing

Abstract: Fish protein represents one of the most widely consumed dietary protein sources by humans. The processing of material from the fishing industry generates substantial unexploited waste products, many of which possess high biological value. Protein hydrolysates, such as fish protein hydrolysates (FPH), containing predominantly di- and tripeptides, are more readily absorbed than free amino acids and intact protein. Furthermore, in animal models, FPH have been shown to possess numerous beneficial properties for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 126 publications
(185 reference statements)
0
22
0
Order By: Relevance
“…On the other hand, one year might not be sufficient time to detect the preventive effect on muscle health. This was one of the first studies assessing MPH in relation to physical function and strength in older adults [ 12 ], and we suggest the following recommendations for future studies: Future studies should be performed on a frailer population or on populations with immobilized older adults. The population that is most in need of help with stimulating MPS is composed of people who are immobilized over a period of time, e.g., after injuries or illnesses affecting mobility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, one year might not be sufficient time to detect the preventive effect on muscle health. This was one of the first studies assessing MPH in relation to physical function and strength in older adults [ 12 ], and we suggest the following recommendations for future studies: Future studies should be performed on a frailer population or on populations with immobilized older adults. The population that is most in need of help with stimulating MPS is composed of people who are immobilized over a period of time, e.g., after injuries or illnesses affecting mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Fish protein supplements in small doses have shown a positive effect on body composition in favor of muscle vs. fat in overweight people, both in a study using 3 g fish protein [ 10 ] and 1.4–2.8 g fish protein hydrolysate [ 11 ]. These doses are small, and the effect might be related to bioactive peptides, rather than the known effect of protein as a source of amino acids [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish-derived protein hydrolysates (FPH) may hold promise as functional foods to promote healthy ageing, metabolic health, and benefit skeletal muscle metabolism in humans [ 30 ], whilst improving economic and environmental efficiency [ 31 , 32 ]. Cordeiro et al [ 33 ] reported rapid and robust post-exercise aminoacidaemia in young individuals following consumption of 0.25 g·kg −1 ·body mass −1 of a Nile tilapia-derived FPH—a response that was similar to WPH.…”
Section: Introductionmentioning
confidence: 99%
“…Cordeiro et al [ 33 ] reported rapid and robust post-exercise aminoacidaemia in young individuals following consumption of 0.25 g·kg −1 ·body mass −1 of a Nile tilapia-derived FPH—a response that was similar to WPH. This suggests that FPH might represent a useful and efficient alternative for the promotion of skeletal muscle anabolism [ 30 ]. Nonetheless, the impact of FPH on amino acid kinetics and anabolic potential remains to be determined in older adults.…”
Section: Introductionmentioning
confidence: 99%